2009
DOI: 10.1183/09031936.00090109
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of tobacco smoke on human airway dendritic cellsin vivo

Abstract: Airway dendritic cells (DCs) play a key role in smoke-related lung diseases; however, the acute effects of tobacco smoke on human airway DCs in vivo are unknown.A total of 16 smokers underwent bronchoalveolar lavage at two time-points: directly after a 4-h period of nonsmoking (no smoke exposure); and directly after a 4-h period during which eight cigarettes were smoked (acute smoke exposure). Using flow cytometry, myeloid DCs (mDCs) and plasmacytoid DCs (pDCs), as well as function-associated surface molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 37 publications
2
52
0
1
Order By: Relevance
“…These results are in accordance with the findings in BAL fluid after acute smoke exposure [28] and indicate that smoking as such does not influence the number of pDCs in the airways and lymphoid follicles. As immature pDCs are present in the mucosal areas of the lung, they can be directly influenced by the effects of cigarette smoke.…”
Section: Discussionsupporting
confidence: 82%
“…These results are in accordance with the findings in BAL fluid after acute smoke exposure [28] and indicate that smoking as such does not influence the number of pDCs in the airways and lymphoid follicles. As immature pDCs are present in the mucosal areas of the lung, they can be directly influenced by the effects of cigarette smoke.…”
Section: Discussionsupporting
confidence: 82%
“…These cDC show prominent expression of the Langerhans' cell markers langerin and CD1a and the costimulatory molecules CD80 and CD86 39 . The effects of cigarette smoke on DC production of IL-8 and prostaglandin E2 appears to be mediated via both oxidative stress and the direct effects of nicotine 40 .…”
Section: Copdmentioning
confidence: 99%
“…It is clear that cigarette smoking per se can lead to increases in the number of lung cDC, even in the absence of overt lung disease 39 . These cDC show prominent expression of the Langerhans' cell markers langerin and CD1a and the costimulatory molecules CD80 and CD86 39 .…”
Section: Copdmentioning
confidence: 99%
“…Havenith et al, 1993;Xia et al, 1995): within 12 hours, the lung derived DCs can be found in the T-cell area of draining mediastinal lymph nodes of the lung. Inflammatory diseases of the human lung are associated with the different phenotypes and the process of the recruitment of the airway DCs (Lommatzsch et al, 2007(Lommatzsch et al, , 2010Geurtsvankessel and Lambrecht, 2008;Vassallo et al, 2010). Regulation of galectin-3 in the lungs may represent one of the multiple potential mechanisms by which galectins contribute to modulation of the innate and acquired immune responses (Maldonado et al, 2011).…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%
“…Highly specialized and notably heterogenous, DCs function as messengers and regulators between innate and acquired immunity (e.g. Reid, 1997;Hart, 1997;Banchereau and Steinman, 1998;Austyn, 1998;Satthaporn and Eremin, 2001;Dzionek et al, 2000;Webb et al, 2005;McKenna et al, 2005;Lommatzsch et al, 2007Lommatzsch et al, , 2010GeurtsvanKessel and Lambrecht, 2008;von Garnier and Nicod, 2009). Because DCs have the ability to induce a primary immune response in resting naïve T-lymphocytes and play a role in the maintenance of B-cell function and antigen memory (recall) responses (e.g.…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%